Nagari Madani: Islamic Favoritism and Religious Freedom in Regional Development in West Sumatera, Indonesia - Taufik, Zulfan; Taufik, Muhammad (Ulumuna, 2023)
The dominance of Islamism in West Sumatra has increasingly strengthened in the post-decentralization period, primarily through the implementation of regional government regulations with Sharia nuances. In contrast to previous studies about the relationship between adat (custom) and Sharia as Minangkabau identity, this study critically examines 1) the way Sharia-based custom is implemented by the Nagari government, which is the smallest unit of local government in West Sumatra; 2) its socio-political implications for religious freedom in the Nagari. This study takes the case of Agam Regency, which has explicitly issued Regent Regulation No. 74 of 2016 concerning the implementation of Nagari Madani. The regulation is a concrete step to realizing religious and traditional life in 82 Nagari, one of 16 sub-districts in the Religious District of West Sumatra. By applying the analytical framework of Grim and Finke on religious favoritism, this study shows that the Nagari Madani policy implemented in Agam Regency is a form of Islamic favoritism. This policy departs from the customary philosophy of adat basandi syara’, syara’ basandi Kitabullah (ABS-SBK), which presupposes that Islam is the primary and principal value for the life of all people in the West Sumatra region. Through the implementation of ABS-SBK, the spirit of Islamization of Minangkabau nature in the development of Nagari provides many conveniences for the majority of Muslims in developing Islamic teachings and accessing funding sources. However, this policy may exclude as fellow citizens who should have the same rights to practice their religion and access development facilities in the Nagari.